2011
DOI: 10.1073/pnas.1019418108
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic chemosensory cells in the trachea regulate breathing

Abstract: In the epithelium of the lower airways, a cell type of unknown function has been termed "brush cell" because of a distinctive ultrastructural feature, an apical tuft of microvilli. Morphologically similar cells in the nose have been identified as solitary chemosensory cells responding to taste stimuli and triggering trigeminal reflexes. Here we show that brush cells of the mouse trachea express the receptors (Tas2R105, Tas2R108), the downstream signaling molecules (α-gustducin, phospholipase C β2 ) of bitter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
323
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(353 citation statements)
references
References 37 publications
18
323
2
2
Order By: Relevance
“…Krasteva et al reported that brush cells in the airway express bitter taste receptors and their downstream signaling molecules such as α-gustducin and PLCβ2 together with acetylcholine synthase (39). Furthermore, the study demonstrated that activation by a bitter substance releases acetylcholine, which eventually decreases the respiratory rate, indicating a biological function of a bitter substance through brush cells.…”
Section: Bitter Signal Transduction In the Gi Tract And Airway Cellsmentioning
confidence: 81%
“…Krasteva et al reported that brush cells in the airway express bitter taste receptors and their downstream signaling molecules such as α-gustducin and PLCβ2 together with acetylcholine synthase (39). Furthermore, the study demonstrated that activation by a bitter substance releases acetylcholine, which eventually decreases the respiratory rate, indicating a biological function of a bitter substance through brush cells.…”
Section: Bitter Signal Transduction In the Gi Tract And Airway Cellsmentioning
confidence: 81%
“…Respiratory chemosensory brush cells express elements of the canonical taste transduction cascade, including the taste-specific G protein α-gustducin, phospholipase C β2 (PLCβ2), and the transient potential receptor cation channel melanostatin 5 (TRPM5) (5,6,(15)(16)(17). These proteins are also expressed in urethras from ChAT-eGFP and WT mice (Fig.…”
Section: Cholinergic Urethral Brush Cells Use the Canonical Taste Tramentioning
confidence: 99%
“…Fluorescence microscopy and immunohistochemistry, pre-embedding immunohistochemistry, and EM, RT-PCR, and acetylcholine measurements were performed as described previously (6,48), with minor modifications. More details are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tracheobronchial epithelium is populated by multiple cell types including basal, ciliated, secretory (mucus or nonmucus), serous cells, brush cells (also termed cholinergic chemosensory cells [10] and solitary chemosensory cells [11]), and neuroendocrine cells. Among these cell types, basal, ciliated, and secretory cells account for the majority of cells within the epithelium and are the focus of our work and that of others.…”
Section: Tracheobronchial Epithelial and Intraepithelial Cell Types Mmentioning
confidence: 99%